Odour effects in mate selection - Muhammad Noor Ridhwan Rasib (2018)
Mate selection is an important aspect of natural life. Much studies has looked into the many variables that may influence such an occurrence. This review article covers how odour may impact mate selection. This is done through looking into the various variables that imapcts olfactory cues: (a) Pheromones; (b) MHC; (c) Menstrual cycle; (d) Fragrances (perfumes, colognes and deodorants); and (e) Food. We then discuss on the real world impacts of odour effects on mate selection, with a large focus on suggesting possible avenues for future directions and research.